Initiation, influence, and impact: adolescents and parents discuss the marketing of gambling products during Australian sporting matches - Pitt, Hannah (BMC Public Health, 2016)
BACKGROUND: Harmful gambling is a significant public health issue. Alongside the rapid diversification of gambling products, are rapid increases in the marketing for specific types of gambling products, such as online wagering. While concern has been raised about the impact of gambling promotions during sporting matches on the gambling beliefs and behaviours of adolescents, very little research has explored adolescents’ and parents’ attitudes towards the marketing of gambling products within sport. METHODS: A qualitative study was conducted with 59 family groups comprising of at least one parent and one adolescent (14–18 years old) in Victoria, Australia. Parents and adolescents were interviewed separately and asked questions relating to their gambling attitudes and behaviours. They were then brought together, and advertising reception techniques were utilised to prompt discussions about the marketing of gambling during sport. A thematic approach to analysis was used, constantly comparing similarities and differences between and across groups. RESULTS: Three main themes emerged. First, was initiation of sport as a platform for the promotion of gambling. Adolescents perceived that the use of embedded promotions (for example during the match) and the use of athletes in gambling promotions were significant mechanisms for creating an alignment between gambling companies and sporting teams and codes. Second, was the influence of marketing messages in creating a perception that gambling was always accessible, and was an integral part of the sporting experience. Third was the impact of marketing messages on adolescent’s discourses about sport. Parents described that they had noticed that wagering, and ‘odds’ discussions, had become embedded in adolescents narratives about sporting matches. DISCUSSION AND CONCLUSIONS: Gambling marketing during sport has significantly increased. While the gambling industry states that it does not aim to intentionally target young people, adolescents are increasingly aware of the relationship between gambling and sport. Future research should explore the impacts and influence of gambling promotions during sport on the gambling attitudes and consumption intentions of adolescents. Effective public health policy is needed to develop comprehensive regulatory frameworks to protect young people from unnecessary exposure to the marketing for this potentially harmful adult product.